Treatment optimization for iron deficiency anemia in pregnant women as a resource to prevent perinatal complications - T. P. Zefirova; R. R. Mukhametova; E. Iu. Iupatov; A. T. Khaertdinov (IRBIS LLC, 2024)
Aim: to assess perinatal maternal and fetal outcomes in women with iron deficiency anemia (IDA), based on the therapeutic approach and timing.   Materials and Methods. A non-interventional cohort study was conducted to assess the effectiveness of treatment with intravenously administered iron preparation in 65 pregnant women diagnosed with moderate-to-severe IDA: at 20-40 weeks of gestation 32 patients received treatment with intravenous iron (main group), 33 women received oral therapy (comparison group). Comparatively analyzed pregnancy course and outcomes based on the therapy protocol were assessed. At the gestational age of 20-23 and 35-40 weeks, clinical data, routine hemogram parameters (hemoglobin level, hematocrit, erythrocyte concentration, erythrocyte indices, total iron binding capacity), serum ferritin-related iron balance, blood viscosity indices within high and low shear rates were investigated.   Results. The groups turned out to be comparable in terms of the major indicators - age, parity, the time of anemia diagnosis, and the average hemoglobin level at the follow-up onset. In main group, after a course of intravenous administration of iron carboxymaltosate, the average hemoglobin level increased from 82.3 ± 6.1 g/L to 98.8 ± 6.8 g/L, for ferritin level - from 9.45 ± 0.28 µg/L to 28.35 ± 0.21 µg/L, total iron binding capacity decreased from 87.5 ± 1.72 mmol/L to 69.8 ± 1.03 mmol/L. In comparison group, the dynamics of indicators was markedly lower: the average hemoglobin level decreased from 87.5 ± 6.4 g/L to 84.5 ± 8.1 g/L, ferritin level decreased from 11.26 ± 0.12 µg/L to 9.47 ± 0.56 µg/L, whereas total iron binding capacity increased from 88.4 ± 0.18 µmol/L to 91.2 ± 1.2 µmol /L. Inter-group perinatal complications differed as well: in comparison vs. main group more often were observed untimely discharge of amniotic fluid (54.5 % vs. 28.1 %; p = 0.031), injuries to the soft tissues of the birth canal (28.1 % vs. 9.1 %; p = 0.048), obstetric bleeding (21.2% vs. 3.1%; p = 0.027), post-delivery infectious complications (24.2 % vs. 6.25 %; p = 0.045). Moreover, in comparison vs. main group there was a higher percentage of neonatal pathologies: fetal growth retardation (39.4 % vs. 15.6 %; p = 0.033), asphyxia at birth (45.5 % vs. 18.8 %; p = 0.015), hemorrhagic disorders (24.2 % vs. 6.3 %; p = 0.045). It was found that IDA was accompanied by deteriorated blood rheological properties manifested as increased viscosity at low shear rates (main group: at a rate of 3 s-1, the viscosity of whole blood was 6.63 ± 0.17 cPs, comparison group - 6.6 ± 0.13 cPs) in contrast to healthy pregnant women (5.54 ± 0.28 cPs) (p < 0.05). After intravenous iron therapy, blood viscosity at a shear rate of 3 s-1 decreased in main group to 5.68 ± 0.23 cPs and did not differ from control (p > 0.05). At the same time, blood viscosity in patients treated with oral drugs had no positive effect and remained at the level of 6.27 ± 0.12 cPs.   Conclusion. The use of intravenous iron carboxymaltosate in pregnant women in the second trimester is an effective approach to treat anemia that alleviates rate of perinatal complications and has a beneficial effect on blood rheological properties.